(untitled) (Journal of Medical & Health Sciences Review, 2025)
The sickle cell disease (SCD) refers to a genetic hemoglobin disease with systemic and ocular complications. The proliferative retinopathy is famous but the cataract formation in SCD is underresearched. The present case report includes a history of a 42-year-old female with homozygous SCD (HbSS genotype) who has reported a four-month history of bilateral progressive loss of visual function. The visual acuity was also reduced to 6/60 in either eye. The slit-lamp biopsy revealed that she had nuclear and cortical cataracts of the advanced type without any trauma, diabetes, or corticosteroids. The existence of intact vitreoretinal structures was ensured by the B-scan ultrasonography. The perioperative optimization was conducted per the hydration, oxygenation, and analgesia after a hematology consultation, and transfusion was not administered. The surgery was performed on intraocular lens implantation under topical anesthesia in sequential phacoemulsification. Recovery was not eventful, and bilateral best-corrected visual acuity of 6/9 was achieved after one month and it is sufficient to have functional independence. The case states that the pathophysiological role of chronic hypoxia, oxidative stress and frequent vaso-occlusive crisis in the acceleration of cataractogenesis in SCD patients decades before the normal population is a factor. Early screening of SCD by ophthalmologists and multidisciplinary perioperative planning and early surgical intervention are the keys to preventing avoidable visual disability and improving the quality of life experienced by the affected patients.